CONSPICUOUS CONSUMPTION: CONTENT ANALYSIS OF WOMEN'S LEADERSHIP IN KAZAKHSTAN MEDIA SOURCES (The Journal of Psychology and Sociology, 2024)
The presented scientific article deals with the analysis and research of women's leadership as one of the aspects of demonstrative consumption in modern Kazakhstani society. The research analysed the content of the most quoted media of the country and popular television channels in order to identify the features of perception of women's leadership in the media environment and its reflection in public opinion. The data obtained show that there is insufficient attention to the problem of women's leadership on television and that women are poorly associated with the concepts of "leader" and "manager". The study also highlights the existing inequality of career opportunities between men and women in the public service. The importance of further research on the role of the media in shaping gender stereotypes and creating conditions for the enhancement of women's status in society is noted. Supporting women's self-expression through the manifestation of social status is seen as a promising direction for achieving women's leadership in Kazakhstan. Such conclusions require further research and the development of active measures in the sphere of social policy to ensure more fair and equal participation of women in the public life of the country.Key words: conspicuous consumption, women's leadership, Maslow's hierarchy of needs, social status, content analysis, media.